Development of a Derivatization Method for Investigating Testosterone and Dehydroepiandrosterone Using Tandem Mass Spectrometry in Saliva Samples from Young Professional Soccer Players Pre- and Post-Training - Mansour A. Alzahrani; Ghareeb O. Alshuwaier; Khalid S. Aljaloud; Colin Gibson; Abedawn Khalaf; Aliyah S. Alhawiti; David G. Watson (MDPI AG, 2019)
In the last decade, high-performance liquid chromatography/tandem mass spectrometry (LC/MS/MS) combined with electrospray ionization (ESI) has been widely used for determining low concentrations of steroids, and derivatization has often been employed to enhance detection. In the present study, endogenous steroids were extracted using a Strata-XL polymeric reverse phase cartridge. The isolated steroids were reacted with 2-hydrazino-1-methylpyridine (HMP) at 50 °C for 30 min. A liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used in a positive mode with multiple reaction monitoring (MRM) for the quantification of testosterone (T) and its precursor, dehydroepiandrosterone (DHEA), in saliva samples collected from twenty young Saudi professional soccer players. The analytes were separated on an ACE Ultracore 2.5 Superphenylhexyl column (150 × 3.0 mm id). The extraction recovery during the pre-treatment was >89% and gave <±20% for inter- and intra-assay precision and accuracy. The limits of quantification (LOQ) were found to be 20 pg/mL for (T and DHEA) and 50 pg/mL for Epitestosterone (EPI). The results showed no significant variation in the concentration of T between pre and post training, whereas DHEA was significantly increased after short-term exercise. These results could indicate that there is no correlation between T and its precursor DHEA level following short term physical activity. EPI concentrations could not be detected with a LOQ of 50 pg/mL in the saliva samples.